THE TEACHER ACHIEVEMENT MOTICATION AS AN INTERVENING VARIABLE IN RELATIONSHIP BETWEEN TEACHER’S PROFESIONALISM, PRINCIPAL’S LEADERSHIP AND TEACHER’S PERFORMANCE OF STATE HIGH SCHOOL IN BANJARMASIN CITY - Damai, Stefanus; Effendi, Rustam; Sulaiman, Sulaiman (Journal of K6, Education and Management, 2019)
The aim of this research is to describe the relationship between teacher professionalism, headmaster leadership, and teachers? performance through the intervening variable which is the teachers? achieving motivation. This research was done with the quantitative method with 228 teachers as the samples who were from the 13 different Senior High Schools in Banjarmasin based on random sampling. Data is taken with the checked questionnaire for its validity and reliability based on the pilot project. Data were analyzed by path analysis with calculations through IBM SPSS 20. The results showed that there was a relationship between teacher professionalism, principals 'leadership, and teacher performance and achievement motivation was intervening between the relationship between teacher professionalism and teacher performance and principals' leadership and performance.